Impact of Total Quality Management Practices on Customer Satisfaction: Perspectives of Medical Device Company (Global Business Management Review (GBMR), 2021)
Customer satisfaction is an asset that should be protected and retained just like any other asset in an organization. The management needs practices that promote customer satisfaction in an organization's service provision. The study objective was to determine the effect of Total Quality Management (TQM) practices in medical device companies in Malaysia on customer satisfaction. This research aimed to establish quality management practices among Malaysia's medical device manufacturing industries and determine their influence on customer satisfaction. The study involved a descriptive overview that undertook a cross-sectional survey design to establish the TQM practices and customer satisfaction in several medical device companies in Malaysia. The study population was employees from various divisions and positions in the medical device industry. Qualitative research methodology has been applied due to the large number of respondents who participated. Data was captured through the interview process and research questionnaire to evaluate the respondents focusing on quality control activities and customer satisfaction in the medical device industry. This qualitative analysis was employed to help this study which seeks to identify cause and effect relationships. Further studies may embark on a larger scale of respondents to better overview the current practices in medical device companies.